DIGITAL PARENTING: PELATIHAN STRATEGI PENGAWASAN ANAK DI ERA GADGET BAGI IBU RUMAH TANGGA DI DESA KELAMBIR V - Tasril, Virdyra; Rizka, Ade; Sulistianingsih, Indri; Sari, Sri Novida (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: The advancement of digital technology has influenced the way parents raise their children, especially amid the widespread use of gadgets today. From an early age, children are becoming accustomed to using digital devices, and without adequate supervision, this can negatively impact their development. This community service activity was designed to enhance the knowledge and skills of housewives in Kelambir V Village in applying a digital parenting approach, particularly in supervising their children's use of gadgets. The activities were carried out through counseling sessions, focused group discussions (FGD), and supervision simulations based on case studies. The training successfully improved the mothers' understanding of the impacts of gadget use, while also fostering their commitment to establishing rules for digital device usage within the family environment. This initiative also supports the creation of a healthy technology use culture at home and strengthens the role of mothers as primary caregivers in today’s digital era. It is hoped that this training can serve as a model of community-based family empowerment practices in rural areas. Keyword: digital parenting; gadgets; digital literacy; housewives Abstrak: Kemajuan teknologi digital telah memengaruhi cara orang tua membesarkan anak, terutama di tengah maraknya penggunaan gadget saat ini. Sejak usia dini, anak-anak mulai terbiasa menggunakan perangkat digital, dan tanpa pengawasan yang memadai, hal ini dapat berdampak buruk pada perkembangan mereka. Kegiatan pengabdian ini dirancang untuk meningkatkan wawasan dan keterampilan ibu rumah tangga di Desa Kelambir V dalam menerapkan pendekatan digital parenting, khususnya terkait pengawasan penggunaan gadget pada anak. Kegiatan ini dilaksanakan melalui penyuluhan, diskusi kelompok terarah (FGD), dan simulasi pengawasan berbasis studi kasus. Pelatihan tersebut berhasil meningkatkan pemahaman para ibu mengenai dampak penggunaan gadget, sekaligus menumbuhkan komitmen mereka untuk menerapkan aturan penggunaan perangkat digital dalam lingkungan keluarga Kegiatan ini turut mendukung terciptanya budaya penggunaan teknologi yang sehat di rumah, sekaligus memperkuat peran ibu sebagai pengasuh utama di zaman era digital sekarang. Pelatihan ini diharapkan menjadi contoh praktik pemberdayaan keluarga berbasis komunitas di daerah pedesaan. Kata kunci: digital parenting; gadget; literasi digital; ibu rumah tangga